What strategies of Algerian public banks face the presence of foreign banks? - Nouara DJEMAH; Lounis OUAOUDIA (Dirassat Journal Economic Issue, 2015)
Since the 1990s, the Algerian authorities have embarked on a vast program of reforms to accompany the transition of the Algerian economy from a planned economy to a market economy. The Algerian banking system, which was hitherto a simple instrument at the service of centralized planning, which played only a passive role in the financing of the national economy, is being given a new turn in the activity of the financial and economic intermediation.